Plectranthus scutellarioides (L.) R.Br. Leaf Extract as Sunscreen, Skin Lightening, and Antiaging - Widyastuti, Widyastuti; Elmitra, Elmitra; Wardi, Epi Supri; Agustin, Diana (Science and Technology Indonesia, 2024)
Plectranthus scutellaroides is a plant with attractive colored leaves. It contains secondary metabolite compounds such as flavonoids and phenolics, which provide skin protection against ultraviolet rays from the sun. The research aims to investigate the activity of P. scutellarioides leaf extract from various variants and different solvents on sunscreen, skin lightening, and anti aging activities. The best extract is formulated in gel dosage form. Each P. scutellaroides leaf was extracted using ethanol, ethyl acetate, and hexane as solvents. The obtained extract was assessed for Sun Protecting Factor (SPF), UVA Protection grade (PA), antioxidant activity, and inhibition of tyrosinase, collagenase, elastase, and hyaluronidase. Determination was conducted in vitro using spectrophotometric methods. The highest sunscreen activity was observed in the ethanol extract Va (Va-ET), which exhibited SPF and PA values of 25.618±0.265, and 0.681±0.007 (star 3), respectively at a concentration of 100 ug/mL. The most significant skin-lightening activity was observed in the ethanol extract Vc (Vc-ET), with an IC50 value inhibiting tyrosinase of 39.059 ug/mL. Regarding the anti-aging activity of the extracts, as determined by their antioxidant activity and inhibition of collagenase, elastase, and hyaluronidase, the most promising extracts were obtained from ethanol extract Va (Va-ET) and ethyl acetate extract Va (Va-EA), with IC50 values of 79.734, 76.838, 143.384, and 122.467 ug/ mL, respectively. The Va-ET was formulated into a gel dosage form, and there was a significant effect of the gelling agent on the SPF value of the extract after formulation (p < 0.05). All extracts exhibit activity as sunscreen, skin lightening, and anti-aging, with the Va-ET showing the highest efficacy. Gelling agents significantly influence the SPF value of extracts after formulation into the gel dosage form. Among them, F3, formulated from the Va-ET of P. scutellaroides using Carbopol-940 as a gelling agent, exhibits the highest efficacy.